2020
DOI: 10.1073/pnas.2011249117
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against central nervous system antigens in a subset of B cell–dominant multiple sclerosis patients

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS), with characteristic inflammatory lesions and demyelination. The clinical benefit of cell-depleting therapies targeting CD20 has emphasized the role of B cells and autoantibodies in MS pathogenesis. We previously introduced an enzyme-linked immunospot spot (ELISpot)-based assay to measure CNS antigen-specific B cells in the blood of MS patients and demonstrated its usefulness as a predictive biomarker for disease activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…The anti-CNS reactivity of B cells from patients with MS was confirmed in a recent study combining ELISPOT and planar protein arrays. 24 Culture supernatants of polyclonally stimulated B cells from a subset of patients with MS identified by ELISPOT as having reactivity to human brain lysate were tested against a broad spectrum of myelin antigens using protein/peptide arrays. Compared with ELISPOT-negative patients and controls, ELISPOT-positive patients with MS demonstrated broader reactivity to the myelin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CNS reactivity of B cells from patients with MS was confirmed in a recent study combining ELISPOT and planar protein arrays. 24 Culture supernatants of polyclonally stimulated B cells from a subset of patients with MS identified by ELISPOT as having reactivity to human brain lysate were tested against a broad spectrum of myelin antigens using protein/peptide arrays. Compared with ELISPOT-negative patients and controls, ELISPOT-positive patients with MS demonstrated broader reactivity to the myelin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between autoantibodies and CNS antigens has been an interesting issue in MS for many years ( 19 ). Regarding detection methods for autoantibodies, tissue-based IFA is a useful screening method to detect the presence of autoantibodies and their target cells in sera from patients with autoimmune neurological syndromes ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these results, the studies are not entirely conclusive since, for instance, Kuhle et al observed that a clear connection between anti-MOG and anti-MBP presence and CIS to MS conversion is not apparent. For instance, Kuhle et al observed that a clear connection between anti-MOG and anti-MBP presence and CIS to MS conversion is not apparent [ 114 ]. Furthermore, Kuerten et al used microarrays to analyze antibodies against 205 myelin antigens in a cohort of 13 MS patients.…”
Section: Classification Of Biomarkersmentioning
confidence: 99%
“…Microarray significance analysis identified a subset of 64 myelin antigens, including MOG and MBP, for which widely elevated levels of anti-myelin autoantibodies could be detected in the plasma of MS patients. Despite this, the authors noted that the levels of significance were not high enough to serve these antibodies as a good predictive clinical biomarker for MS [ 114 ]. Based on these results, and those obtained by other authors (reviewed in [ 115 ]), anti-MOG antibodies would not be adequate biomarkers for the diagnosis or prognosis of MS, but rather for its differential diagnosis with MOG + -CNS demyelinating disease representing a new distinct disease entity.…”
Section: Classification Of Biomarkersmentioning
confidence: 99%